2019
DOI: 10.1038/s41598-019-45326-5
|View full text |Cite
|
Sign up to set email alerts
|

Genes functioned in kleptoplastids of Dinophysis are derived from haptophytes rather than from cryptophytes

Abstract: Toxic dinoflagellates belonging to the genus Dinophysis acquire plastids indirectly from cryptophytes through the consumption of the ciliate Mesodinium rubrum . Dinophysis acuminata harbours three genes encoding plastid-related proteins, which are thought to have originated from fucoxanthin dinoflagellates, haptophytes and cryptophytes via lateral gene transfer (LGT). Here, we investigate the origin of these plastid proteins via RNA sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…2007 ). Transcriptomics and phylogenetic analysis of plastid-related genes in Dinophysis fortii revealed that most such genes are of apparent peridinin plastid origin and thus represent EGTs from the original dinoflagellate plastid ( Hongo et al. 2019 ).…”
Section: Kleptomaniamentioning
confidence: 99%
See 1 more Smart Citation
“…2007 ). Transcriptomics and phylogenetic analysis of plastid-related genes in Dinophysis fortii revealed that most such genes are of apparent peridinin plastid origin and thus represent EGTs from the original dinoflagellate plastid ( Hongo et al. 2019 ).…”
Section: Kleptomaniamentioning
confidence: 99%
“…Intriguingly, the rest of the plastid-associated genes were not only of cryptophyte kleptoplast origin but also of haptophyte origin—including genes related to those of dinoflagellates with permanent tertiary haptophyte plastids (i.e., fucoxanthin dinoflagellates). This suggests that the ancestors of extant Dinophysis engaged in haptophyte kleptoplasty at some point during their evolutionary history ( Hongo et al. 2019 ).…”
Section: Kleptomaniamentioning
confidence: 99%
“…to the host nucleus had already occurred; or specific metabolic connections between the hosts and their ODPs were established among the clade of Nitzschia and Dinothrix spp., and other diatoms cannot be used for photosynthesis in Dinothrix spp. Particularly for the second possibility, some transcriptomic analyses which have targeted kleptoplastic dinoflagellates or dinotoms revealed that very few or no genes have transferred to the host dinoflagellates from their current favorite prey microalgae (Wisecaver and Hackett, 2010;Hehenberger et al, 2016;Hongo et al, 2019). In light of these previous studies, gene transfer might not have a significant effect on diatom selection in dinotoms.…”
Section: Dinothrix Spp Might Possess a Variety Of Origins And Integrmentioning
confidence: 99%
“…Finally, Dinophysis spp. have (presumably) shortlived kleptoplastids derived from prey algae, including Prasinophyceae (Form IB RuBisCO), and, all with Form ID RuBisCO, Cryptophyta, Haptophyta and Ochrophyta (Bacillariophyceae, Dictyochophyceae, Pelagophyceae; Daugbjerg and Henriksen 2001, Park et al 2010, Qiu et al 2011, Nishitani et al 2012, Rial et al 2012, Hongo et al 2018). An Antarctic dinofagellate related to Karenia and Karlodinium has haptophyte kleoplastids (Gast et al 2007).…”
Section: Dinoflagellate Rubisco Diversity Beyond Form IImentioning
confidence: 99%